The role of trust in online lending - Christoph Bertsch; Isaiah Hull; Yingjie Qi; Xin Zhang (Sveriges Riksbank, 2017)
We study the impact of trust on the expansion of online lending in the U.S. over the 2008-2016 period. Using data from the largest platform, we demonstrate that a misconduct-driven decline of trust in traditional banking is associated with a statistically and economically significant increase in online lending at the state level. To the contrary, increased social trust strengthens in-person, bank-based borrowing and informal borrowing, reducing the demand for impersonal online lending. Both of these effects operate primarily through borrowers. We also use a shock that affects only investors to demonstrate that distrust in traditional finance increases participation in online lending.
Keywords: A13; G00; G21; K00; 330; financial development; consumer loans; bank misconduct; FinTech